OBESITAS SENTRAL SEBAGAI FAKTOR RISIKO TERJADINYA PREDIABETES DI KOTA CIM - , YOAN HOTNIDA NAOMI HUTABARAT, Prof. dr. H.Ahmad Husain Asdie, SpPD-KEMD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Obesity is an epidemic global health problems and associated with prevalence of prediabetes, characterized by impaired glucose tolerance (IGT) or impaired fasting glucose (IFG) or both, and its also a significant risk factor for the development of type 2 diabetes mellitus. Objective: This study aimed to determine the relationship central obesity as prediabetes (impaired fasting glucose) risk factor with estimated the ratio prevalens. Methods: Observational analytic with cross-sectional design. The population of this study was community surrounded of public health centers area aged > 18-45 years old that included the inclusion and exclusion criteria, totaling 380 people, 57 men and 323 women. Results: The prevalence of prediabetes in this study was 8.2%, prediabetes with central obesity was 11.9% and prediabetes non central obesity was 3.9%. The prevalence of central obesity was 52.9%, 40.4% in men and 55.1% in women. Bivariat analysis with chi-square showed an association between aged and prediabetes (RP=3,720, CI 95% 1.273 - 10.875, p= 0.011), systolic hypertension with prediabetes (RP=3,368, CI 95% 1,593-7,121, p=0,001), and central obesity with prediabetes (RP=3,332, CI 95% 1,399 -7,934, p=0,004). The results of multivariate analysis with logistic regression showed variables that have relationship with prediabetes was central obesity (RP=2,539, CI95% 1,037 - 6,212, p=0,041), and systolic hypertension (RP=2,268, CI95% 1,034 - 4,975 p=0,041). Conclusion: Central obesity is a risk factor of prediabetes with ratio prevalens 2,5